IN VITRO STUDY OF ANTI-INFLAMMATORY AND ANTIOXIDANT ACTIVITY OF SOME MEDICINAL PLANTS AND THEIR INTERRELATIONSHIP - Rastogi, Shubhi; Iqbal, Mohammed Shariq; Ohri, Deepak (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present work is to study the in vitro anti-inflammatory and antioxidant activity of medicinal plants. The extent and correlation between anti-inflammatory and antioxidant activity have been studied. Method: Methanolic and aqueous extracts of five medicinal plants, namely, Ficus racemosa, Aloe vera, Cannabis sativa, Datura stramonium, and Calotropis gigantean have been taken for in vitro anti-inflammatory and total antioxidant activity. Result: The study showed that the inhibition of protein (albumin) denaturation was maximum in aqueous extract of A. vera with 97.55±1.45%. Proteinase inhibitory action of different plant extracts showed significant action and was found to be maximum in aqueous extract of D. stramonium with 87.89±2.58%. Heat-induced hemolysis showed that maximum inhibition was with aqueous extract of F. racemosa with 90.72±3.33%. When hypotonicity-induced hemolysis activity was done it was found maximum in methanolic extract of C. gigantea with 90.58±3.04%. Anti-lipoxygenase activity was found maximum in methanolic extract of F. racemosa with 94.05±4.24%. When total antioxidant activity was done, it was found highest in F. racemosa (4.38±0.546 mM equivalent of ascorbic acid/g tissue). Conclusion: An overall strong positive correlation between anti-inflammatory and antioxidant activity was observed, indicating that antioxidant activity of the plant species studied might be responsible for their anti-inflammatory property. Further work needs to be undertaken to fully elucidate the antioxidants responsible for anti-inflammatory action and to develop better herbal drug formulations.